Acetyl-11-Keto-β-Boswellic Acid-Loaded Ethosomes as Nanocarriers from a Physicochemical Perspective and in vivo Evaluation - Marbaniang, Daphisha; Gogoi, Niva Rani; Pal, Paulami; Das, Anup Kumar; Jana, Bani Kumar; Saikia, Ananta; Mazumder, Bhaskar (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Ethosomes are elastic nanovesicles made of phospholipids that contain a high concentration of ethanol. It has shown to improve the skin permeability of many drugs due to interactions between the high ethanol. Materials and Methods The optimization and characterization of 3-Acetyl-11-Keto-β-Boswellic Acid (AKBA) loaded vesicular ethosomes included measurements of particle size, entrapment effectiveness, microscopy using SEM and TEM, and the interaction of the drug and excipients using Fourier transform infrared spectroscopy was carried out. FT-IR studies revealed no interaction between the drug and the excipients. Additionally, in vitro drug permeation test utilizing pig ear skin was conducted on ethosomal formulations. E8 (containing 30% alcohol, 2% w/w phospholipid), was chosen for additional skin permeation studies due to its high percentage of drug entrapment (88.43%) and small particle size (129.3±0.75nm). Results The formulation E8 had the greatest amount of drug permeability (73.22%). Furthermore, paw oedema assay using carrageenan induction was used to investigate the in vivo evaluation of the produced formulation. The anti-inflammatory efficiency of ethosomal vesicles containing AKBA was compared to that of AKBA-loaded carbopol gel. Conclusion It revealed that ethosomal had higher anti-inflammatory activity than carbopol gel formulation. Our findings suggest that the developed ethosomal system has the potential to deliver AKBA through the skin.
Keywords: Ethosomes; Transdermal flux; Acetyl-11-keto-beta-boswellic acid; Lipid-based vesicles; Permeation enhancers